Sistem Pakar Deteksi Penyakit Culvularia Dengan Metode Forward Chaining - Panjaitan, Indra Syahputra; Subagio, Selamat; Samsir, Samsir (CSRID (Computer Science Research and Its Development Journal), 2025)
Oil palm diseases generally attack leaves during the seedling phase and can cause major losses if not handled properly. Symptoms that appear include yellow spots that then develop into necrosis, inhibiting seedling growth, and increasing the death rate of plants that during the entire life cycle of plants, from seeds, nurseries, planting, to storage of harvests, plants are never free from disturbances that can inhibit their growth and development. These disturbances can be in the form of pest attacks, infections of disease-causing pathogens, competition with weeds, or unfavorable environmental factors. A researcher from India estimated that crop yield losses were caused by weeds of around 33%, disease-causing pathogens of around 26%, pest attacks of around 7%, rats of around 6%, and damage during storage of around 7%. In other words, biological disturbances such as weeds, pathogens, and pests, as well as abiotic factors such as storage conditions, can cause significant decreases in yields if not managed properly. An expert system is a system that attempts to adopt human knowledge into a computer so that the computer can solve problems as is usually done by experts. While an expert system is a branch of artificial intelligence that uses the special knowledge possessed by an expert to solve certain problems. Forward Chaining is a method of data reasoning that starts from known facts and uses rules (IF-THEN) to reach a conclusion or solution. With this application, it is expected that the community can carry out early treatment and prevention of the disease independently, so as not to worsen the disease in the plant. The expert system is also equipped with a Microsoft Visual Studio solution, a complete application created by Microsoft. In Visual Studio, there are several programming languages ​​that are often used, such as Visual Basic 2008. Visual Studio 2008 Express Edition is very popular as a Windows Application Development Tool.